Standardizing care to manage bleeding disorders in adolescents with heavy menses—A joint project from the ISTH pediatric/neonatal and women's health SSCs. (1st October 2020) - Zia, Ayesha; Kouides, Peter; Khodyakov, Dmitry; Dao, Emily; Lavin, Michelle; Kadir, Rezan Abdul; Othman, Maha; Bauman, Dvora; Halimeh, Susan; Winikoff, Rochelle; Revel‐Vilk, Shoshana
Abstract: Background: Bleeding disorders (BD) are under‐recognized in adolescents with heavy menstrual bleeding (HMB). Objectives: The lack of clinical guidelines and variable symptomatic management of HMB created the imperative to standardize HMB care to identify and manage BD in adolescents. Methods: We convened an international working group (WG), utilized the results of a literature review to define knowledge gaps in HMB care, and used the collective clinical experience of the WG to develop care considerations for adolescents with BD and HMB. We then solicited input on the appropriateness of HMB care considerations from expert stakeholders representing hematology, adolescent medicine, and obstetrics‐gynecology. We conducted an expert panel online, using the ExpertLens platform. During a three‐round online modified‐Delphi process, the expert panel rated the appropriateness of 21 care considerations using a 9‐point scale to designate care as appropriate (7‐9), uncertain (4‐6), or inappropriate (1‐3) covering screening for BD, the laboratory work‐up, and management of adolescents with BD that present with HMB. We used the RAND/UCLA appropriateness method to determine the existence of consensus among the interdisciplinary panel of experts. Results: Thirty‐nine experts participated in the panel. The experts rated fifteen HMB care considerations as appropriate, six as uncertain, and none as inappropriate. Conclusions: The HMB care statements represent the first set of HMB care considerations in adolescents with BD, developed with broad expert input on appropriateness. Although likely to be of interest to a range of clinicians who routinely manage adolescents with HMB, additional research is required in many key areas.